Effects of amino acid substitutions in hepatitis B virus surface protein on virion secretion, antigenicity, HBsAg and viral DNA - Kuan-Hui Xiang; Eleftherios Michailidis; Hai Ding; Ya-Qin Peng; Ming-Ze Su; Li, Yao; Xue-En Liu; Viet Loan Dao Thi; Xian-Fang Wu; William M Schneider; Charles M. Rice; Hui Zhuang; et al. (J Hepatol, 2017)
Background & aims: As important virological markers, serum hepatitis B surface antigen (HBsAg) and hepatitis B virus (HBV) DNA levels show large fluctuations among chronic hepatitis B patients. The aim of this study was to reveal the potential impact and mechanisms of amino acid substitutions in small hepatitis B surface proteins (SHBs) on serum HBsAg and HBV DNA levels. Methods: Serum samples from 230 untreated chronic hepatitis B patients with genotype C HBV were analyzed in terms of HBV DNA levels, serological markers of HBV infection and SHBs sequences. In vitro functional analysis of the identified SHBs mutants was performed. Results: Among 230 SHBs sequences, there were 39 (16.96%) sequences with no mutation detected (wild-type) and 191 (83.04%) with single or multiple mutations. SHBs consist of 226 amino acids, of which 104 (46.02%) had mutations in our study. Some mutations (e.g., sE2G, sL21S, sR24K, sT47A/K, sC69stop (sC69∗), sL95W, sL98V, and sG145R) negatively correlated with serum HBsAg levels. HBsAg and HBV DNA levels from this group of patients had a positive correlation (r=0.61, p<0.001). In vitro analysis showed that these mutations reduced extracellular HBsAg and HBV DNA levels by restricting virion secretion and antibody binding capacity. Virion secretion could be rescued for sE2G, sC69∗, and sG145R by co-expression of wild-type HBsAg. Conclusion: The serum HBsAg levels were lower in untreated CHB patients with novel SHBs mutations outside the major antigenic region than those without mutations. Underlying mechanisms include impairment of virion secretion and lower binding affinity to antibodies used for HBsAg measurements.